2021
DOI: 10.1021/acssuschemeng.1c06772
|View full text |Cite
|
Sign up to set email alerts
|

Ectoine Production from Biogas in Waste Treatment Facilities: A Techno-Economic and Sensitivity Analysis

Abstract: The capacity of haloalkaliphilic methanotrophic bacteria to synthesize ectoine from CH 4 -biogas represents an opportunity for waste treatment plants to improve their economic revenues and align their processes to the incoming circular economy directives. A techno-economic and sensitivity analysis for the bioconversion of biogas into 10 t ectoine·y –1 was conducted in two stages: (I) bioconversion of CH 4 into ectoine in a bubble column biore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Their findings revealed that the optimal concentrations for nitrogen (ammonium phosphate) and carbon sources (sucrose) were determined as 1.38 and 0.67 g/L, respectively. Researchers have also explored various waste materials to enhance ectoine production (Asiri et al 2020;Omara et al 2020;Chen et al 2020a;P erez et al 2021). For instance, Vibrio subsp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their findings revealed that the optimal concentrations for nitrogen (ammonium phosphate) and carbon sources (sucrose) were determined as 1.38 and 0.67 g/L, respectively. Researchers have also explored various waste materials to enhance ectoine production (Asiri et al 2020;Omara et al 2020;Chen et al 2020a;P erez et al 2021). For instance, Vibrio subsp.…”
Section: Discussionmentioning
confidence: 99%
“…The production of ectoine has been achieved using a variety of sources and wastes, including yeast extract, monosodium glutamate, carbohydrates (sugars), nitrogen sources (ammonium salts) and wastes (corn gluten meal, soybean meal, cotton seed meal, sunflower seed meal, glut feed meal, steep corn liquor, crude glycerol and methane) (Onraedt et al 2005;Lang et al 2011;Wei et al 2011;Bergmann et al 2013;Salar-Garc ıa et al 2017;Chen et al 2018;Asiri et al 2020;Omara et al 2020;Dong et al 2021;P erez et al 2021). In microbial fermentation, carbon and nitrogen sources are the most critical factors required for cell growth and for these cells to produce the desired compound.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further on, the use of consortia has been preferred for the production of ectoine from CH 4 in continuous, due to their higher resilience and two times higher ectoine productivities (Cantera et al 2020). In fact, a recent techno-Economic and Sensitivity Analysis of the production of ectoine from biogas in waste treatment facilities has demonstrated that the production of ectoine from biogas has high profitability with a net present value evaluated at 20 years (NPV 20 ) of 33.6 M€ (Pérez et al 2021). Nevertheless, despite the enormous potential of biogas as feedstock for ectoine production, its large-scale production is still constrained by the limitation of CH 4 solubility in liquid medium and gas-liquid mass transfer, eventually resulting in low product titers.…”
Section: Compounds As Alternative Feedstock For Ectoine and Hydroxyec...mentioning
confidence: 99%
“…Based on the TEA result, a process can be evaluated based on specified parameters and assumptions for a multitude of purposes. It had been conducted conventionally over the past two decades for various purposes, ranging from the evaluation of economic factors [i.e., net present value (NPV) (Lubello et al, 2021), payback period (PBP) (Datas et al, 2019), internal rate of return (IRR) (Olszewski et al, 2017;Gönül et al, 2022), return of investment (ROI) (Qian et al, 2014), discounted cash flow rate of return (DFROR) (Phillips et al, 2011), capital cost (Han et al, 2016;Jiang et al, 2020), general costs (Medina-Martos et al, 2020), profit or revenue (Pérez et al, 2021;Wiatrowski et al, 2022), economic potential (Touili et al, 2018;Bagnato and Sanna, 2019), overall economic feasibility (Comidy et al, 2019)], process factors [i.e., energy saving percentage (Kong et al, 2020), process parameter optimization (Yang et al, 2018;Samani et al, 2022), efficiency of operation (Bock et al, 2021)], and environmental factor (Fahmy et al, 2021;Shawky Ismail et al, 2022).…”
Section: Introductionmentioning
confidence: 99%